Linguistic Impoliteness in the Rocky Gerung vs Silfester Matutina Debate on Rakyat Bersuara TV iNEWS - Gufron; Muhammad Nur; Muhammad Syarif Hidayatullah; Nur Latifatul Qalbi; Inni Farhani (Universitas Islam Negeri Palopo, 2025)
This study investigates the deployment of impoliteness strategies in political discourse, focusing on the iNEWS YouTube video “Keras! Rocky Singgung Penjilat, Silfester Emosi hingga Keluar Kata Kasar - Rakyat Bersuara 03/09.” Employing Culpeper's (1996) Impoliteness Theory, the research aims to identify, categorize, and quantify the specific strategies used by the discussants. The quantitative analysis reveals that Negative Impoliteness is the most dominant strategy, accounting for 28.85% of all occurrences, a clear indication that speakers prioritized direct attacks on the opponent’s intellectual credibility and self-worth to increase social distance. Following this were Sarcasm or Mock Impoliteness (23.08%) and Withholding Politeness (21.15%). These findings demonstrate that impoliteness in this public forum is not merely an emotional byproduct but a calculated rhetorical strategy used to assert dominance, attack the opponent's negative face, and shape public perception. The prevalence of these strategies underscores the confrontational nature of modern political debates on digital platforms, where aggressive discourse is strategically employed to gain attention and reinforce ideological positions. The study emphasizes the critical role of impoliteness as a strategic linguistic tool in media-driven political communication. Future research should explore the perlocutionary effects of these strategies on audience reception and their contribution to political polarization in the digital age.